An analysis on accounting students involvement in education hub to community program: student facilitators’ voice/ Noriah Ismail ... [et al.] - Ismail, Noriah; Soo, Carolyn Kum Yoke; Ahmad, Haryati; Ratan Singh, Deepak Singh; Wan Mohd, Wan Nor Hafidzah; Arbin, Norazam; Elias, Suhaidi; Mohd Ariff AlBakri, Intan Safinas (UiTM Cawangan Johor, 2019)
This research aims to find the perception and experience of thirty Diploma in Accounting student facilitators from Universiti Teknologi MARA Cawangan Johor in their involvement in a community service project sponsored by KHIND Starfish Foundation. The project is known as EDU Hub to Community Program. The project was carried out for eight weeks in which the Standard Four and Five students were provided with a special learning modules which focused on providing lessons as well as learning tips and motivation particularly for four important subjects which are English, Bahasa Melayu, Mathematics and Science. A pre-post questionnaires were deployed among the facilitators after the project was conducted to find their perception of the project and the impact it has made on their interpersonal and soft skills as well as learning experience. The findings revealed that the facilitators perceived the project to be very beneficial for them as it helps to develop their interpersonal and soft skills particularly in terms of their ability to carry out social tasks, social interaction, negotiation and cooperative skills with their peers, superiors and the public. Moreover, they claimed that it helped them share their knowledge, experiences, skills and talents not only with the primary school students, but also with their peer group.